A Mini Review of Peer-to-Peer (P2P) for Vehicular Communication - Sumendra Yogarayan; Siti Fatimah Abdul Razak; Afizan Azman; Mohd. Fikri Azli Abdullah (IAES Indonesian Section, 2021)
In recent times, peer-to-peer (P2P) has evolved, where it leverages the capability to scale compared to server-based networks. Consequently, P2P has appeared to be the future distributed systems in emerging several applications. P2P is actually a disruptive technology for setting up applications that scale to numerous concurrent individuals. Thus, in a P2P distributed system, individuals become themselves as peers through contributing, sharing, and managing the resources in a network. In this paper, P2P for vehicular communication is explored. A comprehensive of the functioning concept of both P2P along with vehicular communication is examined. In addition, the advantages are furthermore conversed for a far better understanding on the implementation.